Inhibitory effects of oral Actinomyces on the proliferation, virulence and biofilm formation of Candida albicans. Issue 9 (September 2015) - Guo, Yiqing; Wei, Changlei; Liu, Chuanxia; Li, Duo; Sun, Jun; Huang, Haiyun; Zhou, Hongmei
Highlights We focus on the dysfunction of oral flora antagonistic to Candida as the development of oral candidiasis. Oral Actinomyces have inhibitory effects on C. albicans by affecting proliferation, virulence and biofilm development. Oral Actinomyces may help prevent development of Candida-associated stomatitis.